2020
DOI: 10.1186/s12876-020-01345-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of circulating microRNAs for the diagnosis of hepatitis B virus-associated hepatocellular carcinoma with low alpha-fetoprotein level: a systematic review and meta-analysis

Abstract: Background Alpha-fetoprotein (AFP) has been widely used for many years as a serum marker for hepatocellular carcinoma (HCC). However, AFP has been recognized as having poor sensitivity. More and more studies have concluded that circulating microRNAs (miRNAs) might be a promising biomarker that could complement AFP. However, the diagnostic ability of circulating miRNAs has varied among the studies. Therefore, we performed the present meta-analysis to appraise the diagnostic performance of circulating miRNAs as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In a metanalysis, Peng et al [ 63 ] concluded that among HBV–related HCCs with low AFP levels, circulating miRNAs could be potential valuable biomarkers. For patients with AFP levels < 400 ng/mL, miR-125b and miR-205 demonstrated a sensitivity of 90% while combination of miR-15b and miR-130b had > 90% sensitivity and specificity.…”
Section: Chbmentioning
confidence: 99%
See 1 more Smart Citation
“…In a metanalysis, Peng et al [ 63 ] concluded that among HBV–related HCCs with low AFP levels, circulating miRNAs could be potential valuable biomarkers. For patients with AFP levels < 400 ng/mL, miR-125b and miR-205 demonstrated a sensitivity of 90% while combination of miR-15b and miR-130b had > 90% sensitivity and specificity.…”
Section: Chbmentioning
confidence: 99%
“…For patients with AFP < 400ng/mL, the overall sensitivity and specificity were 0.84 and 0.76 with AUC of 0.88 (95%CI: 0.84–0.90). Hence, miRNAs are attractive HCC markers to detect HBV-associated HCC with low AFP levels[ 63 ].…”
Section: Chbmentioning
confidence: 99%
“…Different miRNAs and miRNA panels have shown good capacity for separating HBV-HCC patients with negative AFP expression from HC and CHB patients (Table 5 ), such as miR-125b[ 23 ], miR-15b + miR-130b[ 9 ] miR-21 + miR-122 + miR-192[ 22 ], and miR-125b + miR-223 + miR-27a + miR-26a[ 30 ]. A meta-analysis suggests that circulating miRNAs have a relatively high diagnostic accuracy in distinguishing HBV-HCC patients with low AFP levels from non-HCC controls[ 40 ]. Therefore, circulating miRNAs may be an ideal potential diagnostic biomarker for HBV-HCC patients with low AFP levels.…”
Section: Dysregulated Mirnas In the Diagnosis Of Hbv-hccmentioning
confidence: 99%